Low-cost laser measurement gauge for real-time quality control of boards and sheets production (Research, Society and Development, 2020)
This paper describes the conception, the development and the testing of a prototype of a simple and versatile device for micro displacement measurement and thickness monitoring of paper sheets and opaque or transparent plastic films during their fabrication. The device works based on triangulation using low power red diode laser beams for the measurements and low-cost Silicon photodiodes for light detection. The system reproductibility was evaluated as well as experimental simulations for thickness variation detection on adhesive tapes were carried out. The results showed that the gauge is capable to detect and measure thickness variations smaller than 5 µm in real time and can be easily implemented in a production system.